Apiaceae Bioferments Obtained by Fermentation with Kombucha as an Important Source of Active Substances for Skin Care - Zofia Nizioł-Łukaszewska; Aleksandra Ziemlewska; Martyna Zagórska-Dziok; Agnieszka Mokrzyńska; Magdalena Wójciak; Ireneusz Sowa (Molecules)
This article attempts to comprehensively assess plants from the Apiaceae family, such as Apium graveolens, Daucus carota or Petroselinum crispum, as raw plant materials with potential uses in cosmetic products with anti-inflammatory and antibacterial effects. The work compares the phytochemical profiles and activity of extracts and ferments from the roots of these plants obtained during fermentation using kombucha. The antioxidant properties of the tested extracts, the effect on the intracellular level of free radicals and their cytotoxicity towards skin cells were compared. Their anti-inflammatory and antibacterial properties were also assessed. The ABTS and DPPH tests indicated the highest antioxidant potential of the carrot ferments, achieving a 55.75% and 74.6% reduction of these radicals, respectively. The resazurin and Neutral Red assays indicated that in most cases, sample concentrations not exceeding 2.5% did not cause a cytotoxic effect, and in the case of a 20-day parsley ferment, they could increase viability by over 40%. The disk diffusion method indicated growth inhibition zones of over 20 mm for some bacteria. The minimum inhibitory concentrations for seven different bacterial strains ranged from 200 to 400 µg/mL. Anti-inflammatory properties were determined using the ELISA method, assessing the level of interleukins 1β, 6 and 10. The obtained results indicate a higher amount of phytochemicals, a lack of cytotoxic effect at lower concentrations of the tested samples and significantly stronger antioxidant, antibacterial and anti-inflammatory properties of the ferments compared to the extracts. This effect depends on the concentration and fermentation time used.